Accuracy of computed tomography to predict extracapsular spread in p16-positive squamous cell carcinoma - Maxwell, Jessica H; Rath, Tanya J; Byrd, James K; Albergotti, William G; Wang, Hong; Duvvuri, Umamaheswar; Kim, Seungwon; Johnson, Jonas T; Branstetter, 4th, Barton F; Ferris, Robert L (The Laryngoscope, 2015)
To determine the accuracy of pretreatment, contrast-enhanced computed tomography (CT) in the diagnosis of extracapsular spread (ECS) in cervical lymph node metastases from p16-positive head-and-neck squamous cell carcinoma (HNSCC). Retrospective observational study. Sixty-five (n = 65) patients diagnosed between 2004 and 2013 with p16-positive HNSCC and with cervical lymph node metastases measuring at least 1 centimeter in diameter on pathological assessment were included. All patients underwent primary surgical treatment. Subjects' preoperative contrast-enhanced neck CT scans were independently assigned a score for the likelihood of ECS (5-point scale) by two board-certified neuroradiologists. Receiver-operating characteristic curves were generated, and optimal sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated for each radiologist. On histological analysis, the majority of patients (58%; 38/65) were found to have ECS, and 29% (19/65) of patients had ≥ three metastatic lymph nodes. For radiologist 1, PPV and NPV for ECS detection were 72% (95% confidence interval (CI), 53%-87%) and 53% (95% CI, 36%-70%), respectively. For radiologist 2, PPV and NPV for ECS detection were 82% (95% CI, 60 %-95%) and 53% (95% CI, 38%-69%), respectively. CT is not a reliable method for determining the presence of ECS in p16-positive HNSCC patients.